Harnessing waterbodies in Dhaka : Exploring the feasibility of floating solar PV to alleviate the energy crisis in Bangladesh - Islam, Md Imamul; Mohd Shawal, Jadin; Al Mansur, Ahmed; Naiem-Ur-Rahman, Md; Maruf, Md Hasan; Mohiuddin, Mohammad Golam; Shihavuddin, Asm S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Addressing the energy crisis in the 21st century is pivotal for sustainable development. In recent years, Bangladesh has had a significant energy crisis due to the scarcity of fossil fuels as an indirect effect of the economic downturn after the COVID-19 epidemic and the ongoing conflict between Ukraine and Russia. The persistent power outages have detrimentally impacted both economic output and investor confidence. The implementation of floating solar photovoltaic (FSPV) plants has emerged as a feasible solution to address the energy crisis in Bangladesh and alleviate the lack of energy resources. This article thoroughly examined the feasibility of FSPV systems regarding technical, economic, and ecological considerations by conducting PVsyst simulations in several appropriate lakes in the Dhaka Metropolitan region. The study found that by harnessing 5% and 10% of the surface area of the selected lakes, it is possible to achieve a DC capacity of 27.5 MW and 55 MW, resulting in an annual power generation of about 48,282.736 MWh and 93,749.817 MWh respectively. The article investigated the economic viability using the levelized cost of energy metric, revealing an average LCOE of $0.17/kWh. Additionally, the study highlights the potential of FSPV systems to reduce yearly CO2 emissions by 29,355.90349 and 56,999.88874 tons by utilizing 5% and 10% resources respectively. This substantial decrease in emissions significantly contributes to the carbon reduction targets of the country. Overall, the research provides valuable insights into bridging the energy gap and emphasizes the viability of FSPV technology as a practical solution to the energy crisis of Bangladesh in line with SDGs.